2019
DOI: 10.5664/jcsm.7834
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Measures and Prediction of Maternal Sleep-Disordered Breathing

Abstract: Study Objectives: Pregnant women are at risk for sleep-disordered breathing (SDB); however, screening methods in this dynamic population are not well studied. The aim of this study was to examine whether anthropometric measures can accurately predict SDB in pregnant women. Methods: Pregnant women with snoring and overweight/obesity were recruited in the first trimester. Anthropometric measures were performed according to the International Standards for Anthropometric Assessment, including a seated neutral and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 61 publications
(52 reference statements)
0
15
0
Order By: Relevance
“…115 Nonetheless, a recently completed trial investigating the impact of atomoxetine, a norepinephrine reuptake inhibitor, and oxybutynin, an antimuscarinic drug, on OSA showed dramatic improvements in the apnea-hypopnea index. 116 The relevance of the currently investigated drugs in the pregnant population is unclear because upper airway function, ventilatory control, and arousal physiology may all be different in this population due to the effect of significantly elevated levels of sex hormones 4 and other pregnancy-specific factors. Hence, there is a need to better understand pregnancy-specific physiology of upper airway and ventilatory control prior to attempting the use of pharmacotherapy in this population.…”
Section: Pharmacologic Interventions In Osamentioning
confidence: 99%
See 1 more Smart Citation
“…115 Nonetheless, a recently completed trial investigating the impact of atomoxetine, a norepinephrine reuptake inhibitor, and oxybutynin, an antimuscarinic drug, on OSA showed dramatic improvements in the apnea-hypopnea index. 116 The relevance of the currently investigated drugs in the pregnant population is unclear because upper airway function, ventilatory control, and arousal physiology may all be different in this population due to the effect of significantly elevated levels of sex hormones 4 and other pregnancy-specific factors. Hence, there is a need to better understand pregnancy-specific physiology of upper airway and ventilatory control prior to attempting the use of pharmacotherapy in this population.…”
Section: Pharmacologic Interventions In Osamentioning
confidence: 99%
“…Hormonal shifts in pregnancy and lactation modify sleep architecture, 2,3 increase neuronal activity, affect respiratory drive, and control fluid distribution. 4 Anatomical and physiological factors such as ligament stretching, uterine contractions, or fetal movement result in sleep disruption and sleep fragmentation. 5 The respiratory system undergoes significant physiological changes that may influence breathing during sleep; namely, functional residual capacity is reduced in late pregnancy, with more pronounced reductions in the supine position.…”
mentioning
confidence: 99%
“… 38 Another three-variable model—using BMI, age, and a measure of tongue enlargement—predicted polysomnography-verified SDB in the first and third trimesters with >85% accuracy. 39 Bourjeily et al 40 examined 100 women with self-reported snoring and BMI >30 during early pregnancy and found a model combining neck circumference and Mallampati classification (a score based on visual assessment of upper airway space) performed with >80% accuracy in identifying SDB.…”
Section: Diagnosis and Screening Of Sdb In Pregnancymentioning
confidence: 99%
“…We provided no information on neck circumference, which is a potential confounder in the relationship between lying in a supine position and disordered breathing during sleep. 26 Finally, the present cohort comprises a low-risk group of pregnant women. It is possible that sleep position may play a role in the association with adverse perinatal outcomes in higher-risk populations.…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the institutional review board of the Tel Aviv Medical Center, and informed consent was obtained from all participants. Women with a singleton, uncomplicated pregnancy who attended a low-risk obstetric surveillance outpatient clinic were recruited at the end of their second trimester (gestational week [25][26][27] between November 2012 and June 2016. All participants completed a questionnaire on medical and obstetric history, smoking exposure history, and current pregnancy complications.…”
Section: Methodsmentioning
confidence: 99%